Effects of accumulated exercise on the stiffness and hemodynamics of the common carotid artery - Liu, Haibin; Shen, Bingyi; Li, Zusheng; Xue, Chundong; Zhao, Hongling; Pan, Xin; Xu, Dong (Frontiers in Physiology, 2024)
Purpose: This research aims to study and compare the effects of moderate-intensity continuous exercise and accumulated exercise with different number of bouts on common carotid arterial stiffness and hemodynamic variables.Methods: Thirty healthy male adults were recruited to complete four trials in a randomized crossover design: no-exercise (CON), continuous exercise (CE, 30-min cycling), accumulated exercise including 2 or 3 bouts with 10-minute rest intervals (AE15, 2×15-min cycling; AE10, 3×10-min cycling). The intensity in all the exercise trials was set at 45%-55 % heart rate reserve. Blood pressure, right common carotid artery center-line velocity and arterial inner diameter waveforms were measured at baseline (BL), and immediately after exercise (0 min), 10min, and 20min.Results: (1) The arterial stiffness index and pressure-strain elastic modulus of the CE and AE15 increased significantly at 0 min, Arterial diameters decreased in AE15 and AE10, all indicators recovered at 10 min. (2) The mean blood flow rate and carotid center-line velocity increased in all trials at 0 min, only the mean blood flow rate of AE10 did not recover at 10 min. (3) At 0 min, the blood pressure in all trials was increased, and the wall shear stress and oscillating shear index of AE10 were different from those in CE and AE15. At 20 min, the blood pressure of AE10 significantly decreased, the dynamic resistance, pulsatility index and peripheral resistance of CE partially recovered.Conclusions: There is no significant difference in the acute effects of continuous exercise and accumulated exercise on the arterial stiffness and diameter of the carotid artery. Compared with continuous exercise, accumulated exercise with more bouts is more effective in increasing cerebral blood supply and blood pressure regulation, and its oscillatory shear index recovers faster. However, the improvement of blood flow resistance in continuous exercise was better than accumulated exercise.